Pengaruh Social Media Marketing, Brand Image Dan Brand Trust Terhadap Purchase Intention: Studi Kasus Pada Produk Skintific - Rafly, Muhammad; Pradana, Mahir (eProceedings of Management, 2024)
The development of technology and the internet has created social media as an effective marketing tool. Social mediaenables two-way communication, reviews, campaigns, and relevant content to interact with consumers. Data fromSimilarWeb indicates a global decline in customer value for Skintific. This study aims to test the effects ofpredetermined variables and seek solutions from previous research. The research applies a quantitative method,involving data collection through research instruments and statistical analysis to test hypotheses. Using a conclusivemodel, the study explores correlations between the studied variables, referring to similar previous research. Datawere obtained through questionnaires distributed to Skintific consumers. The research findings show that, based onpredetermined statistical analysis, the influence of Social Media Marketing on Purchase Intention is significant, BrandImage significantly affects Purchase Intention, and Brand Trust also has a significant impact on Purchase IntentionKeywords-social media marketing, brand image, brand trust, purchase intention, and Skintific.